LppM impact on the colonization of macrophages by Mycobacterium tuberculosis. (11th July 2016) - Deboosère, Nathalie; Iantomasi, Raffaella; Queval, Christophe J.; Song, Ok‐Ryul; Deloison, Gaspard; Jouny, Samuel; Debrie, Anne‐Sophie; Chamaillard, Mathias; Nigou, Jérôme; Cohen‐Gonsaud, Martin; Locht, Camille; Brodin, Priscille; et al.
Summary: Mycobacterium tuberculosis produces several bacterial effectors impacting the colonization of phagocytes. Here, we report that the putative lipoprotein LppM hinders phagocytosis by macrophages in a toll‐like receptor 2‐dependent manner. Moreover, recombinant LppM is able to functionally complement the phenotype of the mutant, when exogenously added during macrophage infection. LppM is also implicated in the phagosomal maturation, as a lppM deletion mutant is more easily addressed towards the acidified compartments of the macrophage than its isogenic parental strain. In addition, this mutant was affected in its ability to induce the secretion of pro‐inflammatory chemokines, interferon‐gamma‐inducible protein‐10, monocyte chemoattractant protein‐1 and macrophage inflammatory protein‐1α. Thus, our results describe a new mycobacterial protein involved in the early trafficking of the tubercle bacillus and its manipulation of the host immune response.